Legal problems to Control the operation of The Edible-nest Swiftlet House - Saelee, Wimonrat; Thaboonma, Vayupak (CRRU Law, Political Science and Social Science Journal, 2025)
The Edible-nest Swiftlet (The Aerodramus fuciphagus) is a protected wild animal under the Wild Animal Conservation and Protection Act, B.E. 2562 (2019) No. 857, whitce does not allow anyone to raise or possess it, but it can be collected of nests by reguesting permission from the Department of National Parks, Wildlife and Plant Conservation. The Edible-nest Swiftlet are considered economic animals because their nests are highly valuaed, which is an important export product to China. Nowaday, there are more businesses operating The Edible-nest swiftlet houses, it affects the environment, communities and people in the nearly areas, such as smells, bird dropping, noise and disease. This research aim to 1) Study the background and concept of the swiftlet house business, problems and impact arising from the swiftlet house business. 2) Study the Wild Animal Conservation and Protection Act, B.E. 2562 (2019), the Public Health Act, B.E. 2535 (1992), and the Building Control Act, B.E. 2522 (1979) which involve the operation of the swiftlet house business. 3) Study of the comparison of Thai law and Malaysian law in relation to swiftlet house 4) Study and analyze the legal issues involved in Controlling the problems arising from the operation of swiftlet house 5) Propose guidelines to improve the laws related to the operation of the swiftlet house to be more appropriate and effective. The research results found that currently, there are no specific laws for the operation of the swiftlet house regarding permission to operate the business, specifying the location, the swiftlet house standards, healthy and environmental management systems. Therefore, there is still a lack of clarity and efficiency in supervision and control. The researcher believes that 1) The Law should be amended to make The Edible-nest Switflet (The Aerodramus fuciphagus) a protected wild animal that can be raised or bred to promote them as a commercial business to generate income for the community and the country. 2) There should be a specific law of enforce the operation of the swiftlet houses, specifying the details clearly. 3) There should be integration from all section, including business operation, local people, and officials from relevant government, to solve problems effectively and fairly for all parties.